GENDER DIFFERENCES IN EMPATHY: A SYSTEMATIC REVIEW OF QUANTITATIVE STUDIES IN EARLY ADULTHOOD IN INDONESIA - Marwati, Sofa; Tira, Usagi Alifa; Asyikin, Muhammad Fatih Nur; Setiyowati, Ninik (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to critically review gender differences in empathy among early adults in Indonesia, considering the influencing factors. Method: A systematic literature review identified relevant articles using predefined keywords through comprehensive Indonesian and international database searches. Inclusion criteria required articles to be published between 2015 and 2025 in reputable journals, involve Indonesian early adult participants, and explicitly address gender-related differences in empathy.  Results: Based on the screening results, 12 articles met the specified criteria. After the analysis, no consistent results were found regarding gender differences in empathy, but there were consistent patterns. The research results indicate that significant differences between men and women can vary depending on the sample involved, the education pursued, and the family background. Novelty: This study maps context-specific empathy differences based on gender within Indonesian culture. It also highlights empathy during early adulthood– a transitional life stage still underexplored in local research, especially from a gender perspective.